2021
DOI: 10.1111/trf.16582
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between a laser lancing device and lancet for capillary blood sampling, capillary blood hemoglobin measurement, and blood typing

Abstract: Background: Blood donor screening includes tests using capillary blood, which is usually obtained by finger pricking using a lancet; however, the lancet has some shortcomings, such as skin puncture pain and needle stick injury.Recently, laser lancing devices for finger-prick sampling have been developed. We compared capillary blood Hb (cHb) levels and blood typing results obtained using a laser lancing device with those obtained using a lancet. Study design and methods: cHb levels, blood typing results, and sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…A recent systematic literature review indicated a high correlation for most antibody testing areas using DBS. Consequently, a wide range of different collection devices have been developed and introduced into clinical practice [ 20 , 21 ]. Here we report the feasibility of the simultaneous measurement of autoantibodies in saliva samples, which could open new avenues for the diagnosis and follow-up of patients with autoimmune conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic literature review indicated a high correlation for most antibody testing areas using DBS. Consequently, a wide range of different collection devices have been developed and introduced into clinical practice [ 20 , 21 ]. Here we report the feasibility of the simultaneous measurement of autoantibodies in saliva samples, which could open new avenues for the diagnosis and follow-up of patients with autoimmune conditions.…”
Section: Discussionmentioning
confidence: 99%